Lords and towns in medieval Europe: the European Historic Towns Atlas project - Simms, Anngret; Clarke, H. B. (Ashgate, 2015)
This volume is based on possibly the biggest single Europe-wide project in urban history. In 1955 the International Commission for the History of Towns established the European historic towns atlas project in accordance with a common scheme in order to encourage comparative urban studies. Although advances in urban archaeology since the 1960s have highlighted the problematic relationship between the oldest extant town plan and the actual origins of a town, the large-scale cadastral maps as they have been made available by the European historic towns atlas project are still necessary if we want to understand the evolution of the physical form of our towns. By 2014 the project consists of over 500 individual publications from over 18 different countries across Europe. Each atlas comprises at least a core-map at the scale of 1:2500, analytical maps and an explanatory text. The time has come to use this enormous database that has been compiled over the last 40 years. This volume, itself based on a conference related to this topic that was held in the Royal Irish Academy in Dublin in 2006, takes up this challenge. ...
"The origin of this work is a conference on the theme "Topography and power in medieval towns", which was held in the Royal Academy in Dublin in 2006" (Introduction)
Keywords: Europe -- Historical geography; Konferenzschrift -- 2006 -- Dublin; Aufsatzsammlung; Geschichte 500-1500; Stadtplanung; Macht; Stadt; Europa; Geschichtsatlas; Stadtplan; Stadtentwicklung